THE EFFECT OF TAX AVOIDATION, EXCHANGE RATE, PROFITABILITY, LEVERAGE, TUNNELING INCENTIVE AND INTANGIBLE ASSETS ON THE DECISION TO TRANSFER PRICING - Nisa Apriani; Trisandi Eka Putri; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to analyze the effect of tax avoidance, exchange rate, profitability, leverage, tunneling incentives and intangible assets on transfer pricing decisions. The dependent variable in this study is transfer pricing which is proxied by the value of the related party transaction (RPT) of sales. The independent variables in this study are tax avoidance, exchange rate, profitability, leverage, tunneling incentives and intangible assets. This study uses secondary data on financial reports or annual reports that have been published by companies on the Indonesia Stock Exchange. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. By using purposive sampling method, the total overall sample in this study is 70 financial statements from 14 companies. The analytical method used uses logistic regression analysis. The results of the analysis in this study indicate that the exchange rate, profitability, leverage, and intangible assets have a positive effect on the company's transfer pricing decision. While tax avoidance and tunneling incentives negatively affect company transfer pricing decisions.